Study of Modulational Instability in Bose-Einstein Condensates with Spin-Orbit Coupling in Staggered Mode - Sasireka, R.; Sabari, S. [UNESP]; Uthayakumar, A.; Tomio, Lauro [UNESP] (My University, 2024)
We study the modulational instability of two-component discrete Bose-Einstein condensates with inter-site spin-orbit coupling in staggered mode. By performing linear stability analysis, we derive new modulational instability conditions and discuss in detail the effect of the inter-site spin-orbit coupling, as well as inter- and intra-component interactions in the staggered mode. The present results, with the analytical predictions, are shown to differ significantly from previous analyses, in the case of intra-site spin-orbit coupled Bose-Einstein condensates.
Keywords: Deep optical lattice; Discrete media; Gross-Pitaevskii equation; Linear stability analysis; Two-component